Renegade - Schmidt, Anna, 1943- (Schmidt, Anna, 1943- Cowboys & Harvey Girls., 2019)
"Lily Travis may be a Harvey Girl, but she's a rebel--and a romantic--at heart. Too bad her impulsive nature led her to marry a man who promised a life of ease and prosperity, only to disappear the very next day. She's kept her secret as best she can, and now she's convinced she'll never find true love...not even with the handsome local sheriff she can't get off her mind. Cody Daniels knows Lily isn't the right woman for a by-the-book lawman with political ambitions. She's brash, headstrong...and entirely too tempting. But when Lily's past catches up with her and the villain she married threatens everything she holds dear, Cody is determined to defend her honor and show her the future they could have together--no matter the consequences." --Provided by publisher.